Association between neutrophil to lymphocyte ratio and Alzheimer's disease in large biobank cohorts - Drzymalla, Emily; Avery, Christy; Palta, Priya; Reiner, Alexander P; Sun, Quan; Raffield, Laura M (Journal of Alzheimer's disease, 2025)
BackgroundNeutrophil to lymphocyte ratio (NLR) is an inflammatory biomarker for chronic disease that also may provide evidence for peripheral innate immune activation in Alzheimer's disease (AD) pathogenesis.ObjectiveThe objective of this study is to assess the association between NLR and AD as a biomarker or potential causal step for AD pathogenesis.MethodsCohorts used for analysis include the UK Biobank (n = 207100; n = 2198 AD cases) and the All of Us research program (AoU, n = 45202; n = 263 AD cases) which allowed for a larger sample size than most previous studies. Cox proportional hazard models were used to assess the association between NLR and AD, including in models adjusting for factors in the UK Biobank Dementia Risk Score. A Mendelian randomization analysis was performed to assess the potential causality between NLR and AD.ResultsNLR was associated with AD in the UK Biobank (HR: 1.03 per 1 SD, 95% CI: 1.01-1.05) but not in AoU (HR: 1.02, 95% CI: 0.92-1.14). A fixed effects model resulted in a pooled HR: 1.03 (95% CI: 1.02-1.05). These effects were robust to adjustment for C-reactive protein, ε4 genotype status, ε2 genotype status, and other AD risk factors. The MR analysis was performed with 214 NLR-associated variants but was not significant (IVW estimate: -0.001, p: 0.99).ConclusionsFindings provide evidence for NLR as a biomarker for AD but not as a causal risk factor.